Analysis of Operational and Financial Feasibility of the Cap Sri Tanjung Shrimp Cracker Business in Kenanga Village, Sindang District, Indramayu - Sahir, Sahir; Akbar, M. Irfan; Faqih, Achmad; Faizen, Hilmy Awalu (International Journal Labs, 2025)
Tanjung, located in Kenanga Village, Indramayu Regency. The research was conducted from May to July 2025 using a quantitative-descriptive approach through a case study method. Primary data were gathered via direct observation of the production process and in-depth interviews with the business owner, while secondary data were obtained from financial records, supporting documents, and relevant literature on agribusiness MSMEs. The research focuses on two main aspects: (1) Operational Feasibility, analyzed using indicators such as production capacity, production process, technology/equipment, and product quality; (2) Financial Feasibility, assessed through financial indicators including Revenue/Cost Ratio (R/C), Benefit/Cost Ratio (B/C), Break-Even Point (BEP), Return on Investment (ROI), and Net Present Value (NPV). The results show that the business operates smoothly by utilizing local raw materials and labor. Financially, it performs well, with monthly revenue of Rp1,056,000,000 and net profit of Rp747,106,708. The R/C ratio is 2.42, indicating that every Rp1 spent generates Rp2.42 in revenue. The BEP is 25.45 kg, far below the actual production of 24,000 kg per month, highlighting strong profitability. ROI stands at 242%, and the NPV is positive at Rp83,941,679,043, confirming long-term viability. The study concludes that Cap Sri Tanjung shrimp cracker business is both operationally and financially feasible. This research provides valuable insights for MSMEs in the agribusiness sector, suggesting strategies for sustainable growth and profitability based on operational efficiency and financial performance.